Dificultades documentales: Experiencias de ausencia de fuentes y archivos en los estudios sociales sobre Lambayeque, Perú (1922-1989) - Caycay Carpio, Renzo Josue (2024)
In the review of a corpus of twelve social studies texts on Lambayeque from the period 1922-1989, there is a consistent declaration of overwhelming difficulties in accessing printed sources and historical archives. I present this difficulty as a tragedy of inequality, which nevertheless defines the ethos and academic identity of studies in this province of northern Peru.